PREVALENCE AND DIAGNOSTICS OF MASTITIS IN COWS - Zainettinova, D. B.; Mukhamadieva, N. N.; Julanov, M. N.; Stefanik, V. Y. (Ғылым және білім №1, 2020)
Employees of the agro industrial complex are faced with the task of reliable providing the country's population with food and agricultural raw materials of good quality. The main sector of agriculture in Kazakhstan, including the East Kazakhstan region, is animal farming and especially cattle breeding, which is conditioned by natural climatic and geographical conditions. The concentration of livestock on large farms, the mechanization of the main production processes, including milking, defined a number of serious problems on prevention of serious diseases. From them breast diseases take a special place which essentially affect the productivity of animals and reduce the quality of milk. Despite the great attention that science and practice pay to the problem of the spread and prevention of udder diseases, the damage caused by them is increasing every year. The main method to prevent udder diseases is scientifically-based, cost-effective management of animal breeding in case of following zoo-hygienic standards of maintenance, feeding and milking that provide a high level of natural resistance of the organism and productivity of animals. The relevance of the studied problems connected with increasing milk yield and the quality of milk obtained continue to be the most relevant. Therefore the prevalence of mastitis, the reasons of their occurrence and diagnostics are of great practical importance. Нами было изучено проявление субклинического и клинических маститов по сезонам года и распространенными формами мастита были субклинические и катаральные маститы. При субклинических маститах изменения в молоке не сильно выражены, но отличаются от молока здоровых коров по химическому составу и физическим свойствам. Воспалительные процессы в молочных железах изменяют физико-химические показатели молока. Маститы приносят большой экономический ущерб хозяйствам страны, необходимо вовремя проводить диагностические исследования. Анализируя данные проведенного исследования можно заключить, что высокий уровень субклинический и клинический мастит показал в осеннее время года. В результате исследования установлена распространенность заболевания и предрасполагающие факторы в этиологии мастита у коров. Результаты исследования показал что, заболеваемость коров маститом повысился при низкой температуре воздуха и большом количестве осадков. Ухудшение погодных условий отрицательно повлиял на дойных коров, что привел к увеличению числа заболевших всеми формами мастита коров . Распространения и профилактики болезней вымени, причиняемый ими ущерб с каждым годом возрастает. Поэтому распространенности маститов, причин их проявления, диагностика имеют большое практическое значение.
Keywords: ветеринария; мастит коров; рк; mastitis; milk; udder; etiology; diagnostics